Broad Spectrum Anti-Quorum Sensing Activity of Tannin-Rich Crude Extracts of Indian Medicinal Plants - Varsha Shukla; Zarine Bhathena (Scientifica)
Quorum sensing (QS) mechanisms have been demonstrated to have significance in expression of pathogenicity in infectious bacteria. In Gram negative bacteria the autoinducer molecules that mediate QS are acyl homoserine lactones (AHL) and in Gram positive bacteria they are peptides called autoinducing peptides (AIP). A screening of tannin-rich medicinal plants was attempted to identify extracts that could interrupt the QS mechanisms in both Gram positive and Gram negative bacteria over a wide range of concentrations and therefore potentially be potent agents that could act as broad spectrum QS inhibitors. Six out of the twelve Indian medicinal plant extracts that were analyzed exhibited anti-QS activity in Chromobacterium violaceum 12472 and in S. aureus strain with agr:blaZ fusion over a broad range of subinhibitory concentrations, indicating that the extracts contain high concentration of molecules that can interfere with the QS mechanisms mediated by AHL as well as AIP.